Memory craft : improve your memory with the most powerful methods in history - Kelly, Lynne, 1951- (Pegasus Books, Ltd., 2020)
Our brain is a muscle. Like our bodies, it needs exercise. In the last few hundred years, we have stopped training our memories and we have lost the ability to memorize large amounts of information<U+2015>something our ancestors could do with ease. After discovering that the true purpose of monuments like Easter Island and Stonehenge were to act as memory palaces, Kelly takes this knowledge and introduces us to the best memory techniques humans have ever devised, from ancient times and the Middle Ages to methods used by today<U+2019>s memory athletes. A memory champion herself, Kelly tests all these methods and demonstrate the extraordinary capacity of our brains at any age. For anyone who needs to memorize a speech or a script, learn anatomy or a foreign language, or prepare for an exam, Memory Craft offers proven techniques and simple strategies for anyone who has trouble remembering names or dates, or for older people who want to keep their minds agile. In addition to getting in touch with our own human and anthropological foundations, Memory Craft shows how all things mnemonic can be playful, creative, and fun.